EFFECTIVENESS OF LISTENING TO MUROTTAL IN REDUCING LEARNING ANXIETY OF STUDENT - Dinda Raihana; Indri Srimulya; Reka Andika; Khoirunnisa; Julia Ayu Anggraini; Sulaiman Indrawan; Febhilah Tri Syarina; Jasmine Annisa Alnilam Cahyani; Anggi Mela Utami; Ahmad Johari (Taqrib : Journal of Islamic Studies and Education, 2023)
The students in 5th-semester often experience this learning anxiety because of the amount of work that builds up with a short deadline and is unable to manage time properly. One attempt to lower a student's anxiety level was by listening to murottal. Hence, the study aims to test the effectiveness of listening to murottal in reducing learning anxiety levels and to know how murottal listening affects the level of anxiety on 5th-semester students at the UIN Raden Fatah Palembange . This kind of research is pre-experiment design the one group precursor posttest design. Samples of as many as 30 students from the faculty of prodi islamic psychology who were in the fifth semester, with sample takings using propotional random sampling. Research instruments in this study use the learning anxiety scale from nilawati, u (2020). Data analysis uses Paired Sample T-Test with the help of version 22.0 of the IBM SPSS application. Studies show that the t test results shown in this study are "0,000 <.05," hence the significant decline between the pre-test and its post-test. The results prove that the action given or experimentation on the Koran's multirottal Koran has a significant or effective impact on reducing the level of learning anxiety on 5th - semester psychology student in raden fatah palembang.